Intra-swash hydrodynamics and sediment flux for dambreak swash on coarse-grained beaches - O'Donoghue, Tom; Kikkert, Gustaaf A.; Pokrajac, Dubravka; Dodd, Nicholas; Briganti, Riccardo (Elsevier, 2016)
The paper reports on dambreak-type swash experiments in which intra-swash hydrodynamics and sediment flux are measured for swash on a coarse sand beach and a gravel beach. Flow velocity and depth are measured using PIV and LIF respectively; the intra-swash sediment flux is measured using sediment traps. Comparison of measured hydrodynamics with the immobile, permeable bed experiments of Kikkert et al. (2013) indicates that bed mobility impacts on the swash hydrodynamics, reducing the maximum run-up by approximately 8% for both beaches, compared to the maximum run-up on the corresponding immobile beach. The measured intra swash sediment flux at a given location is characterised by high flux at the moment of bore arrival, followed by rapid decay during uprush, becoming zero at some time before flow reversal. For the gravel beach, the backwash sediment flux is negligibly small, while for the sand beach the backwash flux increases slowly as the flow accelerates down the beach, and peaks at about the time of maximum backwash velocity. Intra-swash sediment flux calculated using the Meyer-Peter and Müller bed load transport formula, with measured hydrodynamics as input and bed shear stress estimated using both the Swart and Colebrook formulae, is within a factor 2 of the measured intra-swash flux. The agreement between the calculated and measured flux is better for the sand beach than for the gravel beach, and better for uprush than for backwash. For the sand beach there is good agreement between calculated and measured total uprush and total backwash sediment volumes. The agreement is less good for the gravel beach, for which calculated and measured uprush volumes show a similar trend but the calculated backwash volumes over-estimate the (negligible) volumes observed in the experiments.